The Influence of Literacy on Students' Ability to Complete Their Studies in the Department of Islamic Guidance and Counseling - Mutiara Permata Hati Br.Sinaga; Lahmuddin (Yayasan Vifada Cendikia Indonesia, 2026)
Literacy is the ability to locate, evaluate, and effectively utilize information, which is essential for students in completing academic tasks and graduating on time. This study aims to identify students' literacy levels and examine their impact on the timely completion of academic studies in the Islamic Guidance and Counseling Study Program, Faculty of Da'wah and Communication, State Islamic University of North Sumatra, Medan. This research employed a quantitative approach with a correlational design using a Likert-scale questionnaire. The study population consisted of 507 active final-year students and alumni from the Islamic Guidance and Counseling Study Program. A sample of 44 students from the 2021 cohort was selected using the simple random sampling technique. Data were analyzed using descriptive statistical analysis and simple linear regression to examine the effect of literacy (X) on students' ability to complete their studies (Y). The results of the Pearson correlation analysis revealed a very strong relationship between literacy and students' ability to complete their studies (r = 0.984, p < 0.001), with a coefficient of determination (R²) of 0.968, indicating that literacy accounted for 96.8% of the variance in students' study completion. The t-test demonstrated a positive and statistically significant effect (t = 35.597, p < 0.05), with the regression equation Y = 1.427 + 1.182X. These findings indicate that students with higher literacy levels tend to be more independent, focused, and effective in overcoming research-related challenges, thereby enabling them to complete their studies more efficiently. Conversely, low literacy levels constitute a significant barrier to understanding academic materials and completing final research projects. These findings are consistent with those of Zega and Batubara (2024) and Rohman (2022), who reported that digital literacy and information literacy positively contribute to students' timely graduation. Therefore, this study recommends strengthening information literacy programs at the faculty level to enhance students' on-time graduation rates.